Word Formation Process of Business Term in Antara News Website - Widya Sari; Andri Donal (JEE (Journal of English Education), 2021)
The purpose of the research were to analyze the process of word formation found in the online newspaper ANTARA NEWS and to find out what are widely used in word formation process in this news. Word formation process have 10 types those are coinage, borrowing, compounding, blending, clipping, backformation, conversion, acronym, derivation and multiple processes and in this research the researcher analyzed 5 types of word formation such as compounding, acronym, blending clipping, and derivation. The descriptive qualitative method was used in this research to investigate word formation process in Antara news in the business term. The data of this research are words that contained the process of forming English words. The instrument of this research is print out the news from the internet, classifying the word in business term, identifying and analyzing the data as the procedure of the research. The result of this research indicated that are 117 data. There are 3 types of word formation process found in this research such as compounding (9,40%), acronym (5,98%) and derivation (84,62%) . However In this research the researcher did not find blending and clipping process. The function of word formation in this research, there are those that combined to separated word, some are abbreviated of the sentence and affixes process, both of affixes at the front or back of the word. In this research, the researcher found the derivation as the most of word formation process.